Pengaruh Harga dan Produk terhadap Niat Beli Konsumen di Minimarket Lingkungan Politeknik Negeri Bandung - Daffa Bungaran; Mohammad Rizal Gaffar (Masyarakat Ekonomi Syariah Bogor, 2025)
This research endeavors to examine the influence of value and merchandise on consumer purchase intention at the Bandung State Polytechnic Environmental Minimarket. Researchers use a numerical methodology employing descriptive-verification techniques. The sample in this researcrh totaled 382 participants chosen via judgmental sampling methodology. The data were gathered utilizing a Likert-type survey, then assessed for validity and reliability, and subsequently subjected to multiple linear regression, t-test, F-test, and the coefficient of determination via SPSS. The findings indicated that cost exerts a positive and substantial influence on consumer's inclination to purchase. Products also a positive and substantial influence on the inclination to acquire. Concurrently, cost and offering exert a significant impact on consumers' intent to procure. However, product has a greater influence than price. Simultaneously, price and offering exerts a substantial impact on consumers' intent to procure. These outcomes affirm the significance of competitive pricing strategies and improving offering attributes in eliciting the desire to acquire. Researchers advise minimarket managers to focus more on product durability and perceived price value that meets consumer expectations.